The α-η-μ and α-κ-μ Fading Distributions - Fraidenraich, G.; Yacoub, M.D. (2006 IEEE Ninth International Symposium on Spread Spectrum Techniques and Applications, 2006)
In this paper two new fading distributions, the α-η-μdistribution and α-κ-μ distribution, are presented. The α-η-μdistribution includes the α-μ, Nakagami-m, Nakagami-g, Weibull, Hoyt, Rayleigh, Exponential, and the one-sided Gaussian distributions as special cases. The α-κ-μ distribution includes the α-μ, Nakagami-m, Weibull, Rice, Rayleigh, exponential, and the one-sided Gaussian distributions as special cases. Furthermore, it proposes estimators for the involved parameters and uses field measurements to validate the distributions.